2016
DOI: 10.1186/s12884-016-0842-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher maternal leptin levels at second trimester are associated with subsequent greater gestational weight gain in late pregnancy

Abstract: Background: Excessive gestational weight gain (GWG) is associated with adverse pregnancy outcomes. In non-pregnant populations, low leptin levels stimulate positive energy balance. In pregnancy, both the placenta and adipose tissue contribute to circulating leptin levels. We tested whether maternal leptin levels are associated with subsequent GWG and whether this association varies depending on stage of pregnancy and on maternal body mass index (BMI). Methods: This prospective cohort study included 675 pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
43
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 35 publications
(37 reference statements)
11
43
1
4
Order By: Relevance
“…On the other hand, in sheep models, insulin has been demonstrated to be responsible for the regulation of the mRNA leptin concentration [23]. In a previous Gen3G report, we observed that higher 2nd-trimester maternal leptin was associated with greater subsequent GWG in late pregnancy, and this was stronger in overweight women [8], seemingly reflecting a positive feedback loop on maternal energy balance. This may suggest an additional potential mechanism where higher maternal leptin could stimulate a greater energy transfer across the placenta, leading to greater fetal adiposity, especially in overweight women.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…On the other hand, in sheep models, insulin has been demonstrated to be responsible for the regulation of the mRNA leptin concentration [23]. In a previous Gen3G report, we observed that higher 2nd-trimester maternal leptin was associated with greater subsequent GWG in late pregnancy, and this was stronger in overweight women [8], seemingly reflecting a positive feedback loop on maternal energy balance. This may suggest an additional potential mechanism where higher maternal leptin could stimulate a greater energy transfer across the placenta, leading to greater fetal adiposity, especially in overweight women.…”
Section: Discussionmentioning
confidence: 82%
“…About 80% of placental leptin is secreted towards maternal circulation. We previously found that higher 2nd-trimester maternal leptin levels were associated with greater subsequent GWG in late pregnancy [8]. Very little is known about the role of maternal leptin on fetal growth and neonatal adipose tissue accretion.…”
Section: Introductionmentioning
confidence: 99%
“…Встановлену нами відсутність зв'язку зростання лептину в першому триместрі з подальшим ГЗМТ приводять в своїх роботах Walsh et al [13]. На виявлену нами позитивну асоціацію між гіперлептинемією та ГЗМТ і відсотком ЖМТ в другому та третьому триместрах вказують і поодинокі інші дослідження [14], проте вони не враховують рівень гестаційного приросту.…”
Section: проблеми ендокринної патології № 3 2019unclassified
“…Ha arra gondolunk, hogy ebben az időszakban a terhes anyák jelentős súlytöbbletet halmoznak fel, akkor valóban kérdéses ezt katabolikus fázisnak tekinteni. 20,21 (2. ábra).…”
Section: Laboratóriumi éRtékek éS Ami Mögöttük Vanunclassified